2001
DOI: 10.1097/00000542-200109000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the Basolateral Amygdala Complex Block Propofol-induced Amnesia for Inhibitory Avoidance Learning in Rats

Abstract: Discrete BLAC lesions blocked the amnestic effect of propofol. BLAC activity appears to be a requirement for propofol-induced amnesia. This finding suggests that the BLAC is a key brain site mediating anesthetic-induced amnesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…The vast majority of drug and hormone modulations of memory depend critically on amygdala function, and animal studies of general anesthetic-induced amnesia follow this consistent trend in the literature (1,7,9,22). This suggests studying the effects of other anesthetics on human emotional memory processing is warranted.…”
Section: Fig 3 the Pr For Recollection Memory Is Shown (Mean ϯ Sem)mentioning
confidence: 72%
“…The vast majority of drug and hormone modulations of memory depend critically on amygdala function, and animal studies of general anesthetic-induced amnesia follow this consistent trend in the literature (1,7,9,22). This suggests studying the effects of other anesthetics on human emotional memory processing is warranted.…”
Section: Fig 3 the Pr For Recollection Memory Is Shown (Mean ϯ Sem)mentioning
confidence: 72%
“…Level II: Minimizing the perception: An adequate plane of anesthesia requiring the use of bispectral index [36] or other monitoring systems and use of an ideal "DFT cocktail" drug combination are areas that need further exploration. Currently used anesthetic agents like propofol [37] have minimal analgesic effects and could lead to potential "anesthesia awareness." Ketamine, an N-methyl-Daspartate (NMDA) receptor antagonist, may be one of the agents that can be evaluated in DFT testing as it shares both analgesic and amnesic properties [38].…”
Section: Possible Preventive and Therapeutic Interventionsmentioning
confidence: 99%
“…Lesion of the basolateral amygdala has also been demonstrated to block propofol-and benzodiazepine-induced amnesia in animals [100,101]. Although the amygdala may be one of the key structures in anesthetic-induced amnesia, general anesthetics have also been suggested to interact with other neuronal structures involved in the memory process, and a number of studies have shown that general anesthetics decrease synaptic transmission in hippocampal neurons [102][103][104].…”
Section: Amnesiamentioning
confidence: 99%